Strategi Coping: Teori Dan Sumberdayanya - Maryam, Siti (JURKAM: Jurnal Konseling Andi Matappa, 2017)
Coping behavior is defined as individuals’ transactions to cope with the various demands (internal and external). Coping strategies aim to address the situation and demands which pressing, challenging, taxing and exceed the resources (resources). Coping resources affects the coping strategies that will be done in addressing the issue. The aim of this article was to explore further coping stategies mentioned by several scholars, including Stuart and Sundeen (1991), Lazarus and Folkman (1984), as well as Friedman (1998).  Method used was literature review. Result found that coping strategies have two basic forms, namely problem focused form of coping mechanism/direct action and emotion focused of coping/palliative form